Infrastructural Development and TET Fund Participation in some Selected Higher Institutions in Anambra State - Nigeria - Obi , Yves Mary Virginia; Emenike, Ekene; Okoye, Sunday Nonso; Achinike, Daniel Chimaobim (American Journal of Education and Practice, 2024)
Purpose: This study examined TETFund interventions in the development of infrastructure in selected tertiary institutions in Anambra state using Nnamdi Azikiwe University, Federal Polytechnic Oko, and Nwafor Orizu College of Education Nsugbe as areas of study. Materials and Methods: It adopted adopts descriptive survey design wherein structured questionnaire was used to collect information from a sample of 125 participants. With the aid of SPSS version 20.0 tools of analysis, and public good theory, the data generated was extensively analysed and discussed. Findings: Results of the analysis reveal that infrastructural decay persists in the tertiary institutions in spite of the intervention. It reveals also that TETFund does not engage in the rehabilitation of existing infrastructures and focuses on the provision of up-to-date textbooks and construction of new buildings to the neglect of other infrastructures. Implications to Theory, Practice and Policy: Among others, the paper recommends the expansion of TETFund intervention to include rehabilitation of old infrastructures and the diversification of its interventions in new projects to include all forms of infrastructures.